The Impacts of the Stem-Based Inquiry Learning Models on Critical Thinking Ability and Concept Mastery - Yupani, Evi; Widana, I Wayan (Indonesian Research Journal in Education |IRJE|, 2023)
This research aimed to determine differences in critical thinking skills and mastery of science concepts between students who followed the STEM-based inquiry learning model and students who follow expository learning. The population in this research was 209 students in a total sample of 81 students determined through a random sampling technique. Critical thinking data were collected by tests, while the concept mastery data were collected by multiple-choice tests. Data were analysed using MANOVA. The results of the data analysis showed that the value of F was 26.848 with a significance value of 0.000 which was less than 0.05. Therefore, there are differences in critical thinking skills and mastery of concepts between students who study STEM-based inquiry learning models and students who study expository learning models.